2022
DOI: 10.1021/acs.joc.2c02448
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Back Electron Transfer in the Electron Donor–Acceptor Complex-Mediated Visible Light-Driven Generation of α-Aminoalkyl Radicals from Secondary Anilines

Abstract: An additive-free, visible light-driven annulation between N-aryl amino acids and maleimide to form tetrahydroquinolines (THQs) is disclosed. Photochemical activation of an electron donor–acceptor (EDA) complex between amino acids and maleimides drives the reaction, and aerobic oxygen acts as the terminal oxidant in the net oxidative process. A range of N-aryl amino acids and maleimides have been investigated as substrates to furnish the target THQ in good to excellent yield. Mechanistic investigations, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In 2012, employing a ruthenium complex as a photoredox catalyst, Yu and Bian achieved the synthesis of tetrahydroquinoline ( A2 in Scheme 1b) through an analogous radical addition/cyclization pathway, using N,N‐ dimethylaniline, and maleimides [5] . As such, several research groups have reported on annulation reactions using aniline derivatives [6–11] . On the other hand, annulation involving anisole or thioanisole derivatives via a radical addition/cyclization pathway has been reported only by Walton et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, employing a ruthenium complex as a photoredox catalyst, Yu and Bian achieved the synthesis of tetrahydroquinoline ( A2 in Scheme 1b) through an analogous radical addition/cyclization pathway, using N,N‐ dimethylaniline, and maleimides [5] . As such, several research groups have reported on annulation reactions using aniline derivatives [6–11] . On the other hand, annulation involving anisole or thioanisole derivatives via a radical addition/cyclization pathway has been reported only by Walton et al.…”
Section: Methodsmentioning
confidence: 99%
“…[5] As such, several research groups have reported on annulation reactions using aniline derivatives. [6][7][8][9][10][11] On the other hand, annulation involving anisole or thioanisole derivatives via a radical addition/cyclization pathway has been reported only by Walton et al (A3 and A4 in Scheme 1c and 1d, respectively). [12][13] These reactions leverage the single electron oxidation and decarboxylation of aryl acetate to generate α-oxygen methyl radicals or α-thiomethyl radicals.…”
mentioning
confidence: 99%
“…3,4 The optimal reaction conditions involved reacting the maleimide with a large excess of the N,N-dialkylaniline in 1,4-dioxane under irradiation with two 15-W UV compact fluorescent light bulbs (λ max = 366 nm) over 18 h. These researchers proposed that this transformation was facilitated by the formation of an electron donor−acceptor (EDA) complex under the reaction conditions, 5 which was supported by UV− vis absorption spectroscopy, 3 and was consistent with relevant findings from their recent follow-up study. 6…”
Section: ■ Introductionmentioning
confidence: 99%
“…Prior to commencing dedicated experiments to investigate the aforementioned photochemical Povarov-type transformations, we examined the primary literature in order to identify whether germane observations had been made by others. In 2018, Sundén and Hsu reported catalyst-free photochemical Povarov-type reactions between N , N -dialkylanilines and N -alkylmaleimide/ N -arylmaleimide substrates (Figure B). , The optimal reaction conditions involved reacting the maleimide with a large excess of the N , N -dialkylaniline in 1,4-dioxane under irradiation with two 15-W UV compact fluorescent light bulbs (λ max = 366 nm) over 18 h. These researchers proposed that this transformation was facilitated by the formation of an electron donor–acceptor (EDA) complex under the reaction conditions, which was supported by UV–vis absorption spectroscopy, and was consistent with relevant findings from their recent follow-up study …”
Section: Introductionmentioning
confidence: 99%
“…(* corresponds to the excited state).Based on the previous work of Sharma and coworkers, the authors suggested the good polymerization efficiency of 2 and 4a is unlikely to arise from an inefficient back electron transfer[336]. Indeed, back electron transfer in photopolymerization is one of the major drawbacks of the photosensitization approach[337][338][339]. Although well-known, this undesired back electron transfer cannot be anticipated.…”
mentioning
confidence: 99%